Gender-based abuse: the global epidemic - Lori Heise
Gender Based violence-including rape, domestic violence, murder and sexual abuse-is a profund health problem for women across the globe. Although a significant cause of female morbidity and mortality, violence against women has only recently begun to be recognized as an issue for public health. This paper draws together existing data on the dimensions of violence against women worldwide and reviews available literature on the health consequences of abuse. It argues that the health sector has an important role to play in combatting violence against women through increased research, screening and referral of victims, and behavioral interventions. Any strategy to confrnt violence must address the root causes of abuse in addition to meeting the immediate needs of victims. This means challenging the social attitudes and beliefs that undergird men's violence and renegotiating the balance of power between women and men at all levels of society.